Birefringence studies in ferroelectric liquid crystal doped with titanium dioxide nanoparticles - Budaszewski, Daniel (Photonics Letters of Poland, 2024)
The following research work determines experimentally the birefringence of the ferroelectric liquid crystal (FLC) W212 doped with titanium dioxide nanoparticles (TiO2 NPs) of low concentration in the FLC matrix. For this reason, the method based on transmittance measurements through the investigated sample in the polariscope setup is applied. Optical microscopy observations indicated good alignment quality of the FLC-NP mixtures in planar glass cells. The birefringence measurements clearly indicate that TiO2 NPs reduce the birefringence of the W212 FLC for wavelengths in the measured range between 500 nm and 700 nm. The results can be valuable especially in the context of modelling and designing a new class of FLC-based optical elements both in planar cells and photonic liquid crystal fibers. Full Text: PDF References A. Yoshizawa, "Ferroelectric Smectic Liquid Crystals," Crystals 14(4), 350 (2024). CrossRef S.K. Gupta, D. Budaszewski, and D.P. Singh, "Ferroelectric liquid crystals: futuristic mesogens for photonic applications," Eur. Phys. J. Spec. Top. 231(4), 673 (2022). CrossRef R.B. Meyer, L. Liebert, L. Strzelecki, and P. Keller, "Ferroelectric liquid crystals," J. Phys. Lett. 36, 69 (1975). CrossRef N.A. Clark, T.P. Rieker, "Smectic-C ’’chevron,’’ a planar liquid-crystal defect: Implications for the surface-stabilized ferroelectric liquid-crystal geometry," Phys. Rev. A 37(3), 1053 (1988). CrossRef V.G. Chigrinov, H.-S. Kwok, H. Hasebe, H. Takatsu, and H. Takada, "Liquid-crystal photoaligning by azo dyes (Invited Paper)," J. Soc. Inf. Disp. 16(9), 897 (2008). CrossRef V.G. Chigrinov, V.M. Kozenkov, and H.-S. Kwok, Photoalignment of Liquid Crystalline Materials, Wiley-SID Series in Display Technology (John Wiley & Sons, Ltd, 2008). CrossRef D. Budaszewski, K. Wolińska, B. Jankiewicz, B. Bartosewicz, T.R. Woliński, "Spectral properties of photo-aligned photonic crystal fibers infiltrated with gold nanoparticle-doped ferroelectric liquid crystals," Crystals 10(9), 1 (2020). CrossRef S.P. Yadav, R. Manohar, S. Singh, "Effect of TiO 2 nanoparticles dispersion on ionic behaviour in nematic liquid crystal," Liq. Cryst. 42(8), 1095 (2015). CrossRef D. P. Singh, K. Agrahari, A.S. Achalkumar, C.V. Yelamaggad, R. Manohar, M. Depriester, "Preparation and photophysical properties of soft-nano composites comprising guest anatase TiO2 nanoparticle and host hekates mesogens," J. Lumin. 205, 304 (2019). CrossRef B.P. Singh, C.-Y. Huang, D.P. Singh, P. Palani, B. Duponchel, M. Sah, R. Manohar, K.K. Pandey, "The scientific duo of TiO2 nanoparticles and nematic liquid crystal E204: Increased absorbance, photoluminescence quenching and improving response time for electro-optical devices," J. Mol. Liq. 325, 115130 (2021). CrossRef D. Budaszewski, D.P. Singh, T.R. Wolinski, "Enhancement of electro-optical response of photonic crystal fibers infiltrated with ferroelectric liquid crystal doped with titanium dioxide nanoparticles," Opt. Express 31(18), 29942 (2023). CrossRef E. Pozhidaev, S. Torgova, V. Barbashov, V. Kesaev, F. Laviano, A. Strigazzi, "Development of ferroelectric liquid crystals with low birefringence," Liq. Cryst. 46(6), 941 (2019). CrossRef B.G.S. Rao, K. Mallika, S.T. Ha, and S.S. Sastry, "Birefringence and order parameter studies in ferroelectric liquid crystals using laser transmission technique," Z. Für Naturforschung A 76(2), 163 (2021). CrossRef M. Kawaida, T. Yamaguchi, and T. Akahane, "Measurement of Refractive Indices of Ferroelectric SmC* Liquid Crystal by the Fabry-Perot Interference Method," Jpn. J. Appl. Phys. 28(9A), L1602 (1989). CrossRef A. Messaadi, M. del M. Sánchez-López, P. García-Martínez, A. Vargas, I. Moreno, "Optical system for measuring the spectral retardance function in an extended range," J. Eur. Opt. Soc.-Rapid Publ. 12(1), 21 (2016). CrossRef E. Pozhidaev, S. Torgova, M. Minchenko, C. Augusto Refosco Yednak, A. Strigazzi, and E. Miraldi, "Phase modulation and ellipticity of the light transmitted through a smectic C* layer with short helix pitch," Liq. Cryst. 37(8), 1067 (2010). CrossRef K. Kurp, M. Czerwiński, M. Tykarska, "Ferroelectric compounds with chiral (S)-1-methylheptyloxycarbonyl terminal chain - their miscibility and a helical pitch," Liq. Cryst. 42(2), 248 (2015). CrossRef K. Kurp, M. Czerwiński, M. Tykarska, and A. Bubnov, "Design of advanced multicomponent ferroelectric liquid crystalline mixtures with submicrometre helical pitch," Liq. Cryst. 44(4), 748 (2017). CrossRef K. Kurp, M. Czerwiński, M. Tykarska, P. Salamon, and A. Bubnov, "Design of functional multicomponent liquid crystalline mixtures with nano-scale pitch fulfilling deformed helix ferroelectric mode demands," J. Mol. Liq. 290, 111329 (2019). CrossRef R. Basu and A. Garvey, "Effects of ferroelectric nanoparticles on ion transport in a liquid crystal," Appl. Phys. Lett. 105(15), 151905 (2014). CrossRef